Peripheral arterial bypass in pediatric patients: Literature review and a case of complex trauma in a 5-year-old boy - Fabrizio Minelli, MD, PhD; Francesco Sposato, MD; Marta Minucci, MD; Francesca De Nigris, MD; Giovanni Tinelli, MD; Yamume Tshomba, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2025)
Peripheral arterial bypass in pediatric patients is a rare but essential surgical intervention, often performed in cases of trauma, congenital abnormalities, or severe vascular occlusion. Unlike adults, children present unique anatomical and physiological challenges owing to their smaller vessel size, rapid growth, and different responses to vascular injury and repair. This review aims to provide an overview of current knowledge, surgical techniques, and outcomes of peripheral arterial bypass in pediatric patients, with a focus on trauma-induced vascular injuries. Additionally, we present a case study involving a 5-year-old patient with a complex traumatic injury requiring arterial bypass.